ANALISIS RISIKO OPERASIONAL BERDASARKAN PENDEKATAN ENTERPRISE RISK MANAGEMENT (ERM) PADA KELONG MELAMUN - Haryani, Dwi Septi; Fauzar, Selvi; Ratnasari, Sri Langgeng; Ardian, Novra; Abriyono, Octojaya; Saputra, Eka Kurnia (STIE PEMBANGUNAN TANJUNGPINANG, 2025)
The purpose of this research is to analyze and identify operational risks to understand the resulting impacts and determine actions that need to be taken as anticipation and prevention measures for potential operational risks at Melamun Villa. This study employs a descriptive qualitative research approach. Data collection techniques used in this research include interviews, observations, and documentation. The sample for this study was selected through purposive sampling and consisted of one Person In Charge (PIC) namely Mr. Acep and one employee of Melamun Villa. The research findings indicate that operational risks occurring at Melamun Villa consist of 16 operational risks, starting from risk identification, risk analysis, risk assessment, risk management, to recommendations for risk handling. The recommendations that the author can provide to Melamun Villa are to implement the outlined risk prevention measures to reduce and mitigate potential risks within the operational scope of Melamun Villa.